Business transformation towards sustainability - Anna-Luisa Müller; Regina Pfleger (Business Research, 2014)
Sustainability is becoming increasingly important in today's corporate world and can contribute to the current and future success of organizations. Integrating ecological, social, and economic objectives into corporate decisions is a key success factor for transformation towards sustainability. As sustainability is not achieved by single actions, but rather is an on-going process, decision-makers must have means to analyze the current state of an organization. For this, we first illustrate how companies can structure the field of action for the transformation towards sustainability. Furthermore, we propose a decision model to determine how sustainability actions should be implemented in accordance with the paradigm of value-based management, i.e., considering their economic effects. We illustrate the application of the approach using the example of a German medium-sized company.
Keywords: F64; M14; Q56; 330; Sustainability; Corporate sustainability; Economic valuation; Transformation; Decision-making; Triple bottom line; Sustainability maturity level